Added Value of Cognition in the Prediction of Survival in Low and High Grade Glioma - van Kessel, Emma; Schuit, Ewoud; Huenges Wajer, Irene M. C.; Ruis, Carla; De Vos, Filip Y. F. L.; Verhoeff, Joost J. C.; Seute, Tatjana; van Zandvoort, Martine J. E.; Robe, Pierre A.; Snijders, Tom J. (Frontiers in Neurology, 2021)
Background: Diffuse gliomas (WHO grade II-IV) are progressive primary brain tumors with great variability in prognosis. Our aim was to investigate whether pre-operative cognitive functioning is of added value in survival prediction in these patients. Methods: In a retrospective cohort study of patients undergoing awake craniotomy between 2010 and 2019 we performed pre-operative neuropsychological assessments in five cognitive domains. Their added prognostic value on top of known prognostic factors was assessed in two patient groups (low (LGG) and high grade gliomas (HGG)). We compared Cox proportional hazards regression models with and without the cognitive domain by means of loglikelihood ratios tests (LRT), discriminative performance measures (by AUC) and risk classification (by Integrated Discrimination Index (IDI)). Results: We included 109 LGG and 145 HGG patients with a median survival time of 1490 and 511 days, respectively. The domain memory had significant added prognostic value in HGG as indicated by a LRT. The cumulative AUC for HGG with memory included was 0.78 and without cognition 0.77, IDI was 0.043 (0.000 - 0.102). In LGG none of the cognitive domains added prognostic value. Conclusions: Our findings indicate that memory deficits, revealed with neuropsychological examination, are of additional prognostic value in HGG to other well-known predictors of survival.